রণদা প্রসাদ সাহা স্মারকগ্রন্থ - সাহা, রণদা প্রসাদ, ১৮৯৬-১৯৭১; আনিসুজ্জামান
Contributed articles on the life and works of Raṇadā Prasāda Sāhā, 1896-1971, philanthropist, social worker and businessman from Bangladesh; commemorative volume.